2006
DOI: 10.1111/j.1474-919x.2006.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Do territorial and non‐breeding Australian Magpies Gymnorhina tibicen influence the local movements of rural birds in New Zealand?

Abstract: Australian Magpies Gymnorhina tibicen sometimes attack and kill other birds in New Zealand. Here we assess how Australian Magpies influence the local distribution of other birds in New Zealand and identify the members of an Australian Magpie population that display the most agonistic acts. We conducted regular observations on six territorial breeding groups and three non-breeding flocks of Australian Magpies for 1 year to determine (1) if other birds avoid flying or foraging close to Australian Magpies, (2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Conversely, there is also anecdotal evidence that invertebrate prey abundances in some areas are actually higher where there are magpies, which may be the result of other predators being driven from these areas by magpies (McCaskill, 1945). While this hypothesis has not been tested, rural bird species were shown to avoid being in close proximity to territorial magpies in one New Zealand study (Morgan et al, 2006a; but also see Borowske et al, 2012).…”
Section: Positive Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, there is also anecdotal evidence that invertebrate prey abundances in some areas are actually higher where there are magpies, which may be the result of other predators being driven from these areas by magpies (McCaskill, 1945). While this hypothesis has not been tested, rural bird species were shown to avoid being in close proximity to territorial magpies in one New Zealand study (Morgan et al, 2006a; but also see Borowske et al, 2012).…”
Section: Positive Impactsmentioning
confidence: 99%
“…McIlroy, 1968). Swamp Harriers appear to be regarded as a serious threat to magpies and have been attacked more frequently than any other bird species in New Zealand (Morgan et al, 2005(Morgan et al, , 2006a. Furthermore, Morgan et al (2006b) reported that Swamp Harriers were an important predator of bird nests, predominantly the Eurasian Blackbird (Turdus merula) and Song Thrush (Turdus philomelos), in rural New Zealand and accounted for 36% of recorded predation events.…”
Section: Positive Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was some strong evidence for a lack of competition in interactions with the Common Myna (Parsons et al 2006;Lowe et al 2011;Borowske et al 2012), Common Starling (Williamson and Gray 1975;Vierling 1998) and Mute Swan (Conover and Kania 1994). There was correlative evidence that the Australian Magpie reduced the abundance of native species in New Zealand (Morgan et al 2006). There was correlative evidence that the Common Myna is a threat to the Seychelles Magpie-Robin (Copsychus sechellarum) and that the Common Myna and Red-vented Bulbul are a threat to the Tahiti Monarch (Pomarea nigra) ( Table 1; see 'Evidence for threats involving introduced species', below).…”
Section: Interference Competitionmentioning
confidence: 99%
“…Both are assigned to demeanour class A due to reputations for adversely impacting other birds through interference competition or, more rarely, predation of adults and/or nestlings (Barrington 1995(Barrington , 1996Tindall 1996;Morgan et al 2005). Documented impacts include avoidance of magpies by New Zealand birds (Morgan et al 2006) and aggressive dominance of mynas over native Australian parrots (Pell and Tidemann 1997). Pigeon (33 cm; 400 g) and dove (28 cm; 140 g) (also exotics) are comparably sized to magpie and myna respectively but were assigned to demeanour class B because they are not considered aggressive toward other species (Heather and Robertson 1996).…”
Section: Introductionmentioning
confidence: 99%